DETERMINAN TINDAKAN TAX AVOIDANCE PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - IVAN PRIMUS; RIAN SUMARTA (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
The purpose of this study is to analyze empirical evidence regarding the factors that influence tax avoidance in manufacturing companies listed on the Indonesia Stock Exchange during the period 2017-2019. The variable used in the company such as return on asset, leverage, institutional ownership, firm size, political connection, audit quality, and audit committee. The population of this study are manufacturing companies listed on the Indonesia Stock Exchange during the period 2017-2019. The sample of this research are selected with using purposive sampling method, with the number of samples that match the criteria of 243 data. Data were analyzed using multiple regression method. The results showed that return on asset, leverage, and political connection have influence to tax avoidance. While, other independent variable do not have influence to tax avoidance.